Losing sleep over mitochondria: a new player in the pathophysiology of fatal familial insomnia. (January 2017) - Glatzel, Markus; Sepulveda‐Falla, Diego
Abstract : This commentary highlights the study by Frau‐Mendez and coworkers in this issue of Brain Pathology (xxx) in which the authors show evidence for involvement of mitochondria in the pathophysiology of fatal familial insomnia (FFI). Using genetic, biochemical and morphological means, they provide a comprehensive picture of the degree of mitochondrial damage in FFI and show that this leads to increased oxidative stress. This adds FFI to the growing list of dementias with mitochondrial involvement. Future studies will have to address the causality dilemma of which came first, mitochondrial damage and subsequent neurodegeneration or vice versa. Either way, these data provide the basis to devise novel therapeutic strategies for FFI.